An unsatisfactory status quo and promising perspectives: why links between brain activity and personality remain elusive and what we need to change to do better. (February 2022) - Wacker, Jan; Paul, Katharina
Highlights: The replicability of associations between personality and measures of brain activity is too low. Reasons include insufficient sample sizes, lacking standardization and complex analysis routines for brain data. Addressing these issues requires a decisively collaborative approach to research. Abstract : Based on a brief review of frequently investigated associations between measures of brain activity and personality, we argue that such links remain elusive. The following features of previous research in this field may account for the scarcity of replicable findings: (1) A focus on broad heterogeneous traits, (2) low reliability of some brain activity measures, (3) lack of well-founded theories, (4) small sample sizes, and (5) undisclosed flexibility in complex preprocessing/analysis routines for brain activity data. Furthermore, we argue that whereas (1) and (2) can be addressed within a typical single-lab study, resolving the remaining (and probably more serious) issues will benefit considerably from close cooperation among researchers with similar interests during all stages of the research cycle. We conclude by describing the 'CoScience' approach to cooperative research. Our initial application thereof will hopefully prove instrumental in moving the field forward.